농어촌산업정책 추진체계 개편 방안 - 이동필 (한국농촌경제연구원, 2008)
The purpose of this study is to figure out the actual state and problems of the rural industrial policy and introduce the new promotion structure of rural industrial policy in Korea. Its contents consist of 1) defining the definition of rural industry and scope of rural industrial policy, 2) finding the state and problems of rural industrial policy, 3) suggesting the strategies to vitalize rural industry, and 4) developing the guideline and promotion structure of rural industrial policy. The results are that first, the definition of rural industry is food, manufacturing, and service industries handling, treating, processing or packaging primary products, tradition and culture, and landscape in the locality, etc. Second, the problems of rural areas are decreasing rural population, lack of young labors, and increasing gap of income and development between urban and rural areas in Korea. On this situation, the new rural industrial policy is needed. Strategies are 1) to promote local-specialized industry through select and focus, 2) to find and industrialize local assets differently, 3) to exploit local resources for development of rural tourism and related services, 4) to improve local investment conditions and attract and localize more businesses, 5) to make local industrial networks through industrial clusters, and 6) to introduce block grant system and partnership between agriculture and other industies. On new industrial policy system, the central government focuses on consultation and evaluation. The local governments make their own development plans of rural industries, and develop the endogenous local specialized industries based on local assets because it is an important alternative to promote the secondary and tertiary industries in rural areas. The policies to promote it in rural areas have been considered as a powerful instrument for a long time. Researchers: Dong-phil Lee, Kyeong-duk Kim, Mi-ryung Song, Yong-lyoul Kim, Kwang-sun Kim, and Kyung-eun Choi Research period: 2008. 5 - 2008. 12 E-mail address: ldphil@krei.re.kr